JUNIOR HIGH SCHOOL AT SEVENTH GRADE STUDENTS - Nita Syah Umar; Masitowarni Siregar; Nora Ronita Dewi (TRANSFORM : Journal of English Language Teaching and Learning, 2019)
This research is aimed at analyzing the reading materialson the quality of English textbook Bright published by Erlanggafor the first grade studentsof junior high school.This study was designed as a documentary analysis in the form of descriptive qualitative research, in which the result would be described in the form of words without any statistical calculation. The data were collected from the reading section in the textbook. As supplementary tools of the instrument, forms of checklist were used during the research analysis. The result showed that the reading materials in Bright textbook were appropriate with the criteria of qualified English textbook suggested by PusatPerbukuan, Ministry of National Education. There were only two nonconformities found in the textbook: (a) there were some reading materials which were not presented in the textbook and (b) there were no reading materials which could encourage the development of technology and arts.Key words: analysis, relevance, reading materials, textbook, the 2013 curriculum